Teachers’ Reflection: Does The Instructional Technology Implementation Transform Learning? - Tri Mulyati (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
The development of the digital era requires teachers to insert technology into English instruction. Teachers must be able not only to use the internet and computer software but also to implement technology appropriately in the teaching and learning process in order to help students achieve learning objectives. Many teachers have done inserting technology into English instruction. In addition, research on technology integration in English class has been mushrooming since years ago. However, the evaluation dealing with the implementation of technology in English instruction is limited. This research aims at evaluating how teachers use technology in the teaching and learning process. The evaluation focuses on whether the use of technology has enhanced students’ learning experiences or transformed students’ learning experiences. Four levels of the SAMR model (Substitution, Augmentation, Modification, and Redefinition) are used to assess the implementation. Here, the researchers gauged information from six English teachers of the senior high school in Banyuwangi regency concerning how they use technology in the teaching and learning process.